An Innovative Designed Velocimeter Application for Set Net Fishery - Cheng-Chang Chiu; Teh-Lu Liao; Chiung-Hsing Chen; Hsiang Li (Journal of Marine Science and Engineering, 2023)
This article is aimed at the problems encountered by the fishing ground of set nets in Taiwan when the set net operators need to work when the weather is bad at sea. We developed a velocimeter that can be placed in the ocean for a long time and change sensing directions with the flow direction. The self-designed velocimeter has advantages, such as simple operation, low cost, and easy maintenance. With wireless monitoring and an early warning system, it can monitor current velocity, flow direction, sea temperature, and displacement. The data is transmitted back to the operator through the radio transmission module as a basis for dispatching personnel to go out to sea for fishing. To prevent the set net from drifting into the open sea due to bad weather, a GPS module is used to monitor the current location of the set net. If the waves wash away the set net, the warning signal can be received the first time to prevent the floating set net from endangering the safety of ship navigation and the survival of marine life. This innovative technology aligns with SDG 14, which aims to “conserve and sustainably use the oceans, seas, and marine resources for sustainable development”.